Investigations into the Antibacterial Activity of the Silver-Based Antibiotic Drug Candidate SBC3 - Matthias Tacke; Bettina Schaible; Siddappa Patil; Francesca Paradisi; Frauke Hackenberg; Claire Healy; Stephen V. Gordon; Michael A. Sharkey; James P. O'Gara (MDPI AG, 2012)
The synthesis of N-heterocyclic carbene (NHC) silver(I) acetate complexes with varying lipophilic benzyl-substituents at the 1 and 3 positions starting from 4,5-diphenylimidazole, opened a new class of antibiotic drug candidates. These NHC-silver(I) acetate derivatives exhibit interesting structural motifs in the solid state and proved to be soluble and stable in biological media. The leading candidate, SBC3, which was known to exhibit good antibacterial activity in preliminary Kirby-Bauer tests, was tested quantitatively using minimum inhibitory concentrations. NHC-silver(I) acetate complexes were found to have MIC values ranging from 20 to 3.13 μg/mL for a variety of Gram-positive, Gram-negative and mycobacteria tested. These values represent good antibiotic activities against potential pathogens when compared to clinically approved antibiotics. Most striking is the fact that SBC3 is active against methicillin-resistant Staphylococcus aureus with a MIC value of 12.5 μg/mL.